Towards Physical Layer Security Systems Design Using Game Theory Approaches - Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2017)
With the huge develop of low consumption wireless devices both for industry and human wellness and comfort, such as Wireless Body Area Network for health active care and Wireless Sensors Networks for industry environments, new challenges are proposed for the both industry and scientific community. Security is one of this matters. Given the specific characteristics of the low consumptions modern devices, particular security mechanisms must be developed. Here we model a Physical Layer Security mechanism with Cooperative Jamming using Game Theory, in order to go deep into the study on how security of wireless low consumption devices can be improved. Main results shows that certainty on how Secrecy Capacity will behave on its lower and upper bounds is improved by the use of the mixed strategies suggested by the Second Order Cone Programming problem. © 2017 IEEE.